Clean energy from waste : fundamental investigations on ashes and tar behaviours in a two stage fluid bed-plasma process for waste gasification /: fundamental investigations on ashes and tar behaviours in a two stage fluid bed-plasma process for waste gasification. ([2016]) - Materazzi, Massimiliano
No abstract available